2004
DOI: 10.21236/ada515247
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Friction Stir Processing on the Microstructure and Mechanical Properties of Fusion Welded 304L Stainless Steel

Abstract: A variation of FSW, friction stir processing (FSP), has been used to modify selected regions of materials to enhance specific properties while eliminating fusion welding defects such as porosity, cracking, and the cast microstructure. The combination of fusion welding defects and high tensile residual stresses caused by the solidification of the molten weld pool adversely affect the post weld service integrity. FSP has been demonstrated to eliminate many of these problems while at the same time improving the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Both FSW and FSP have been studied extensively for their ability to create favorable properties in metal alloys [13][14][15][16][17][18][19], most of which have been aluminum alloys. While we have not found research literature on the use of FSP to "heal", or repair, stress corrosion cracks in existing welds, one study by Sterling demonstrated that FSP can be used to process over existing arc welds in austenitic stainless steel, to enhance the mechanical properties of the weld [20]. For stress corrosion crack repair of irradiated stainless steel, lower peak temperatures would favor the use of FSP over fusion welding processes like GTAW, because the helium bubbles present in the material would have a lower driving force to diffuse to grain boundaries in the HAZ.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Both FSW and FSP have been studied extensively for their ability to create favorable properties in metal alloys [13][14][15][16][17][18][19], most of which have been aluminum alloys. While we have not found research literature on the use of FSP to "heal", or repair, stress corrosion cracks in existing welds, one study by Sterling demonstrated that FSP can be used to process over existing arc welds in austenitic stainless steel, to enhance the mechanical properties of the weld [20]. For stress corrosion crack repair of irradiated stainless steel, lower peak temperatures would favor the use of FSP over fusion welding processes like GTAW, because the helium bubbles present in the material would have a lower driving force to diffuse to grain boundaries in the HAZ.…”
Section: Introductionmentioning
confidence: 93%
“…But if FSP is a potential solution for weld repair of irradiated stainless steel, there remains the potential challenge of sigma phase and chromium carbide formation, which have been reported in friction stir welded 304L stainless steel along the advancing side of the stir zone [21]. Although others have reported preferential etching along this same region of the stir zone, they also report large variability, depending on the welding conditions [20,22]. Sigma and chromium carbide phases are well known to reduce the corrosion resistance of austenitic stainless steel [21][22][23], and need to be suppressed if FSP is to be employed for weld repair.…”
Section: Introductionmentioning
confidence: 99%
“…Colin J. Sterling [8] highlighted the effects of Friction tir Processing (FSP) on the microstructure and mechanical properties of fusion welded 304L stainless steel. The FSP had been successfully applied as a method to alter the microstructure and hence the mechanical properties of arc welded 304L stainless steel.…”
Section: Friction Assisted Welding Processesmentioning
confidence: 99%
“…-Improvement of mechanical properties by modifying fusion welds in 304L stainless steel and 5083 and 6061 Al alloys [6,15,21].…”
Section: Z=sexp(q/rnmentioning
confidence: 99%